2014
DOI: 10.1002/uog.14690
|View full text |Cite
|
Sign up to set email alerts
|

Performance of screening for aneuploidies by cell‐free DNA analysis of maternal blood in twin pregnancies

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 28 publications
5
120
0
1
Order By: Relevance
“…Although the total fetal fraction of twin pregnancies might be higher than that of singletons10, the individual contribution from each twin is generally lower than that of a singleton8, 9; however, there may be exceptions. In our study, the average combined fetal fraction of both twins (16.1%) was higher than determined previously for singletons over similar gestational‐age ranges (12.6%; P  = 0.001)21, and higher still than the average fetal fraction for a single twin (7.8%; P  < 0.0001), consistent with the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the total fetal fraction of twin pregnancies might be higher than that of singletons10, the individual contribution from each twin is generally lower than that of a singleton8, 9; however, there may be exceptions. In our study, the average combined fetal fraction of both twins (16.1%) was higher than determined previously for singletons over similar gestational‐age ranges (12.6%; P  = 0.001)21, and higher still than the average fetal fraction for a single twin (7.8%; P  < 0.0001), consistent with the previously mentioned studies.…”
Section: Discussionmentioning
confidence: 93%
“…Traditionally, prenatal aneuploidy screening options have been less robust for twin pregnancies than for singletons6, whereas the miscarriage risk associated with invasive diagnostic procedures is higher in twins7. Preliminary data have suggested that NIPT is a feasible test option for twin gestations8, 9, 10. Currently, due to the paucity of reported studies in twins, professional societies and others have called for more studies on NIPT performance in twin gestations11, 12, 13, 14.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also sufficient data to suggest that cfDNA testing is feasible in twin pregnancy, although it seems to be associated with a higher failure rate than in singleton pregnancy 2 .…”
Section: Concerns With Performance Of Screening For Aneuploidy By Celmentioning
confidence: 99%
“…Apart from twin pregnancy, other potential causes of failure and discordant results of cfDNA analysis have been identified: fetoplacental mosaicism, maternal chromosomal abnormalities, vanishing twin, maternal weight, conception by in-vitro fertilization (IVF), low fetal DNA fraction and technical errors 2,3 .…”
Section: Concerns With Performance Of Screening For Aneuploidy By Celmentioning
confidence: 99%